Assessment of in-cylinder pressure in diesel engines using novel combustion indices. Issue 1 (1st January 2021) - Kaisan, Muhammad Usman; Narayan, S.; Ismail, Najib Aminu; Dambatta, Yusuf Suleiman
Abstract: Efficient monitoring of combustion process is a key for regulating emissions from engine as well as achieving fuel economy. Various non-intrusive methods of diagnosis for engines include monitoring of noise, and vibrations emitted are attractive options that are cheap, reliable, and need no modifications in the engine set up under test. Combustion process occurring inside combustion chamber of engine provides important information about cyclic efficiency, heat losses, as well as noise and vibration (NVH) performance of engines. Earlier NVH aspects were thought to closely correlate with the development of in-cylinder pressure inside combustion chamber. However, there have been contradictions to this idea prompting the need for further evaluations. The presented work discusses a novel methodology that may be used for analysis of in-cylinder pressure development during the combustion process for a diesel engine. The in-cylinder pressure development in a small-sized diesel engine was analyzed with the aim to extract information about various indicators that characterize the development of combustion processes. Novel indices were developed based on noise, pressure, and vibrations signature of engines, which were much more correlated to combustion process development. The correlative relationship shows the effectiveness of the proposed methodology for condition monitoring for engines.